From Spreader to Predator: Killing Weed Seeds with the Combine. Issue 5 (18th September 2021) - Flessner, Michael L.; Mirsky, Steven B.; Schwartz‐Lazaro, Lauren M.; Bagavathiannan, Muthukumar V.; VanGessel, Mark J.; Shergill, Lovreet S.; Ackroyd, Victoria J.; Rubione, Claudio G.
Abstract : Faced with the daunting task of herbicide resistance management, Australian farmers developed various systems to target weed seeds during crop harvest. These systems are collectively called harvest weed seed control (HWSC). Despite being relatively unheard of in the U.S., currently more than 80% of Australian farmers practice HWSC. This article provides an overview of the six HWSC systems and the research conducted to date in U.S. cropping systems. This article also includes information for implementing HWSC, what weeds to target, potential costs, and where to find equipment. Earn 0.5 CEUs in Integrated Pest Management by reading this article and taking the quiz at https://bit.ly/3jcbPTq . View all CEUs online at https://web.sciencesocieties.org/Learning‐Center/Courses .